Enhancing learning methodologies in the clinical pharmacokinetic course through student-driven insights and suggestions / Nur Wahida Zulkifli ... [et al.] - Zulkifli, Nur Wahida (Faculty of Pharmacy, 2024)
The clinical pharmacokinetics (CPK) course can be quite challenging and difficult for students to understand its applications, as it involves a combination of abstract yet complex concepts and mathematical calculations. Studies have reported that the conventional lecture-based learning process in CPK often results in a poor understanding, especially when it comes to apply the knowledge to real cases. This study aimed to identify strategies to improve the current learning methodology by using self-developed, validated online questionnaires among 37 fourth-year undergraduate pharmacy students who failed their CPK course in midsemester test at UiTM Puncak Alam, Selangor. We analysed and interpreted the data through descriptive analysis. The majority of students (91.9%) found online quizzes to be the most engaging tool for learning CPK, with 89.2% choosing to include feedback and marks for their answers. Most of them preferred new learning materials that covered both basic concepts and applications-based (86.5%), featuring colourful pictures and diagram interfaces (70.3%) and being accessible anytime and anywhere (83.8%). These preferences have proven to be more effective in enhancing knowledge. The students understood the topics better, which helped improve their engagement and grades. While developing and incorporating educational games into the current CPK course can be time-consuming, the results can be tremendous, transforming the current pharmacy curriculum into something more innovative and fun. Further research related to the development and implementation of alternative learning materials based on these preferences can be conducted to assess its effectiveness in improving students’ performance. Therefore, it is crucial to incorporate the insights of students when enhancing the current learning methodology in the future.